Grupa pracownicza jako przedmiot i podmiot motywowania [Polish] [Work Group as an Object and Subject of Stimulation] - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1990)
The article reviews the book, "Grupa pracownicza jako przedmiot i podmiot motywowania," by Alicja Kozdroj.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

British and Norwegian Offshore Industrial Relations : Pluralism and Neo-Corporatism as Contexts of Strategic Adaptation - Matejko, Alexander J. (Relations industrielles / Industrial Relations, 1990)
This article reviews the book, "British and Norwegian Offshore Industrial Relations : Pluralism and Neo-Corporatism as Contexts of Strategic Adaptation," by Svein S. Andersen.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z